2022
DOI: 10.1111/bjop.12582
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical responding to male versus female other‐race categories in 9‐ to 12‐month‐old infants

Abstract: Faces can be categorized along various dimensions including gender or race, an ability developing in infancy. Infant categorization studies have focused on facial attributes in isolation, but the interaction between these attributes remains poorly understood. Experiment 1 examined gender categorization of other‐race faces in 9‐ and 12‐month‐old White infants. Nine‐ and 12‐month‐olds were familiarized with Asian male or female faces, and tested with a novel exemplar from the familiarized category paired with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…In addition, 12-month-old infants did not show evidence of forming category representations by sex/gender for other-race faces (Damon et al, 2022). Finally, 5-to 6-year-olds raised in a multiracial population exhibited an own-race recognition effect for male faces, but recognized female faces equally from multiple race groups (Tham et al, 2017).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, 12-month-old infants did not show evidence of forming category representations by sex/gender for other-race faces (Damon et al, 2022). Finally, 5-to 6-year-olds raised in a multiracial population exhibited an own-race recognition effect for male faces, but recognized female faces equally from multiple race groups (Tham et al, 2017).…”
Section: Introductionmentioning
confidence: 79%
“…For instance, at 3–4 months of age an own‐race advantage was present for female, but not male faces, but at 8–9 months of age an own‐race advantage was present for both male and female faces (Tham et al., 2015). In addition, 12‐month‐old infants did not show evidence of forming category representations by sex/gender for other‐race faces (Damon et al., 2022). Finally, 5‐ to 6‐year‐olds raised in a multiracial population exhibited an own‐race recognition effect for male faces, but recognized female faces equally from multiple race groups (Tham et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Perceptual narrowing is a developmental process by which visual discrimination capabilities become more “fine-tuned” to frequently encountered stimuli across the first year of life (Kelly et al, 2007 , 2009 ; Scott et al, 2007 ; Pascalis et al, 2020 ). Many mechanisms have been proposed to underlie perceptual narrowing for own-race faces, including familiarity, experience-dependent socio-cultural factors, and the development of category representations (Quinn et al, 2016 ; Markant and Scott, 2018 ; Marquis and Sugden, 2019 ; Pascalis et al, 2020 ; Damon et al, 2022 ). There does appear to be an innate component for increased visual attention to faces, as evidenced by newborns who, within a few hours from birth, exhibit a visual preference for faces and face-like stimuli over other types of stimuli (Goren et al, 1975 ; Johnson et al, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both behavioral and neural studies of the ORE additionally lack sample diversity, particularly for Black, Hispanic/Latino, or Indigenous populations (Serafini and Pesciarelli, 2022 ). Of the infant ORE studies reviewed here, 12 included homogenous samples of White infants (Sangrigoli and De Schonen, 2004 ; Kelly et al, 2005 , 2007 ; Heron-Delaney et al, 2011 ; Spangler et al, 2013 ; Macchi Cassia et al, 2014 ; Fassbender et al, 2016 ; Quinn et al, 2016 ; Krasotkina et al, 2020 ; Hillairet de Boisferon et al, 2021 ; Clerc et al, 2022 ; Damon et al, 2022 ), four included homogenous samples of East Asian infants (Kelly et al, 2009 ; Liu et al, 2015 ; Tham et al, 2019 ; Ujiie et al, 2021 ), and only three included any Black, Hispanic, or bi-/multi-racial infants (Bar-Haim et al, 2006 ; Sugden, 2016 ; Hwang et al, 2021 ). The brief review included here is further supported by a recent meta-analysis, which found that over 60% of samples in the infant face discrimination literature were conducted using a homogenous sample of White infants, and another ~25% were conducted using a homogenous sample of East Asian infants (Sugden and Marquis, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Next, Damon et al (2023) study small infants, promoting an understanding of the early development of social categories in the first year of life. In 9 and 12 months old White infants, they find that categorization of facial gender is delayed and asymmetric especially for other‐‘race’ faces; while female Asian faces elicit novel category preferences after familiarization with male Asian faces, male Asian faces (when shown after familiarization with female Asian faces) do not – challenging the idea that ‘race’ and gender categories are perceived independently in infants.…”
mentioning
confidence: 99%